PERTUMBUHAN STEK PUCUK TANAMAN JABON PUTIH (Anthocephalus cadamba (Roxb.) Miq.) SETELAH DIRENDAM DALAM URIN KAMBING (Capra aegagrus) - Mukarlina, Eka Widiana, Riza Linda, (Jurnal Protobiont, 2016)
Jabon (Anthocephalus sp.) is native species of Indonesia and the cultivation of white jabon in west Kalimantan is still rare. One of the efforts to increase the production of jabon is through vegetative propagation shoot cutting. Propagation through shoot cutting often fails, in which the roots cannot grow. One of the ways of overcoming such failure is by providing exogenous growth regulator, namely, goat urine. This research aimed to find out the effect of the concentration of goat urine (Capra aegagrus) and soaking time on the growth of the shoot cuttings of white jabon. This research used a completely randomized factorial design (CRD) i.e. the factor of concentration (A) consisting of 4 levels of 0%, 6%, 8%, 10%, 12% and the factor of soaking time (B) consisting of four levels, i.e. 0 min, 5 minutes, 10 minutes and 15 minutes. The treatment was repeated three times. The research findings indicated that adding goat urine concentration of 12% and 15 minutes soaking time generated the average root number of 29 pieces, the plant height of 20.33 cm, thewet weight of 16.33 grams and the dry weight of 3.46 grams, and the average number of leaves of 9 pieces, which were obtained from the treatment of a concentration of 10% and a soaking time of 15 minutes.